PENGARUH INSENTIF TERHADAP LOYALITAS KERJA KARYAWAN BANK BRI KANTOR WILAYAH PEKANBARU - Akbar, Fauzan; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine Influence Of Incentive Towards Employee Loyality on BRI Regional Office Pekanbaru. Distribute questionnaires to 91 respondents who are employees at Bank BRI Regional Office Pekanbaru. Base on analysis seen that the implementation of the incentive has been done well and had the right to carry out at Bank BRI Regional Office Pekanbaru. Base on analysis seen that the implementation of loyalty has been done well and had the right to carry out at Bank BRI Regional Office Pekanbaru. Based on the results obtained analyst tÂ¬count value amounted to 10.898 and t-table 1.986. As well as pvalue of 0.000 <0.05. Because t-count> tÂ¬tabel and pvalue value smaller than the value of alpha 0.05, then the hypothesis that there is significant influence work incentives to the loyalty of employees. It concluded that the hypothesis Implementation incentives significantly influence employee loyalty Bank BRI Regional Office Pekanbaru acceptable. Rated R Square of 0.572 which indicates that employment incentives is able to explain the changes in the value of employee loyalty amounted to 57.2%, while the remaining 42.8% is influenced by variables that are not observed in this research model.Keywords: Incentive, Employee Loyality